Negotiating Authenticity and Climate Change in Heritage Gardens - Grönlund, Emma; Seiler, Joakim (FormAkademisk, 2023)
With this paper we explore and discuss the priorities of and possible goal conflicts between authenticity and climate change in heritage gardens. How can climate change mitigation, adaptation, resilience, and cultural heritage conservation be combined in heritage gardens? Our study was guided by the following research question: How do gardeners negotiate climate change and authenticity in heritage gardens? From Rachel Carson's Silent Spring in the 1960s through to the 2002 report Gardening in the Global Greenhouse and the recent Gardening in a Changing World in 2022 mankind's impact on the environment and the emerging climate change has been the focus of increasing attention. By investigating and interviewing multiple gardeners our objective was to pinpoint common challenges, as well as what can be learned from one another within the field of gardening and heritage conservation. The case study method was adopted for this study, involving three head gardeners in the United Kingdom. Interviews were conducted with Joseph Atkin at Aberglasney Gardens, Claire Greenslade at Hestercombe Gardens, and Steve Lannin at Iford Manor about their expertise and knowledge. The gardeners expressed concern regarding climate change and the challenges it poses. The interviewees shared their experience with drought, reduced use of pesticides and herbicides, and the peat legislation in relation to their role as head gardeners. We argue that authenticity and the traditional gardening practised before the advent of power tools, plastic, peat issues, and uninformed transportation can be part of the solution to loss of biodiversity and climate change. This paper identifies some of the obstacles encountered in relation to negotiating questions of authenticity and climate change in heritage gardens.